A Hardware Efficient Random Number Generator for Nonuniform Distributions with Arbitrary Precision - Christian de Schryver; Daniel Schmidt; Norbert Wehn; Elke Korn; Henning Marxen; Anton Kostiuk; Ralf Korn (International Journal of Reconfigurable Computing)
Nonuniform random numbers are key for many technical applications, and designing efficient hardware implementations of non-uniform random number generators is a very active research field. However, most state-of-the-art architectures are either tailored to specific distributions or use up a lot of hardware resources. At ReConFig 2010, we have presented a new design that saves up to 48% of area compared to state-of-the-art inversion-based implementation, usable for arbitrary distributions and precision. In this paper, we introduce a more flexible version together with a refined segmentation scheme that allows to further reduce the approximation error significantly. We provide a free software tool allowing users to implement their own distributions easily, and we have tested our random number generator thoroughly by statistic analysis and two application tests.